A ANALISIS KOMPARATIF PANDANGAN SAYYED HOSSEIN NASR DAN MULYADHI KARTANEGARA TENTANG INTEGRASI SAINS DAN ISLAM SERTA RELEVANSINYA BAGI PEMBAHARUAN PENDIDIKAN ISLAM - Khusnah, Sifaul; Rossidy, Imron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study examines the integration of science and Islam through a comparative analysis of the perspectives of Seyyed Hossein Nasr and Mulyadhi Kartanegara and explores their relevance for the renewal of Islamic education in the modern era. The problem addressed in this research is the persistent dichotomy between religious knowledge and modern science within Islamic educational institutions, which has resulted in intellectual fragmentation and a decline in spiritual and ethical orientation. The objective of this study is to analyze and compare the epistemological, ontological, and axiological foundations of both thinkers regarding the integration of science and Islam, as well as to identify their implications for the reform of Islamic education. This research employs a qualitative library research method, utilizing primary sources from the works of Nasr and Kartanegara, supported by relevant books, journal articles, and academic studies. Data were analyzed through descriptive, interpretative, and comparative approaches. The findings reveal that Seyyed Hossein Nasr emphasizes the concept of scientia sacra, advocating the resacralization of knowledge and the reintegration of spiritual and ethical dimensions into modern science. Meanwhile, Mulyadhi Kartanegara focuses on epistemological reconstruction by integrating sensory perception, rational intellect, and spiritual intuition within a unified Islamic worldview. The study concludes that the synthesis of both perspectives offers a comprehensive framework for the renewal of Islamic education, combining spiritual depth with epistemological rigor to address contemporary educational challenges. ABSTRAK Penelitian ini mengkaji integrasi sains dan Islam melalui analisis komparatif pemikiran Seyyed Hossein Nasr dan Mulyadhi Kartanegara serta relevansinya bagi pembaharuan pendidikan Islam di era modern. Permasalahan utama yang dikaji adalah masih kuatnya dikotomi antara ilmu agama dan ilmu umum dalam sistem pendidikan Islam, yang berdampak pada fragmentasi keilmuan serta melemahnya dimensi spiritual dan etika. Penelitian ini bertujuan untuk menganalisis dan membandingkan landasan epistemologis, ontologis, dan aksiologis kedua tokoh dalam memahami relasi sains dan Islam, serta merumuskan implikasinya bagi reformasi pendidikan Islam. Metode yang digunakan adalah penelitian kepustakaan (library research) dengan pendekatan kualitatif, menggunakan karya-karya Seyyed Hossein Nasr dan Mulyadhi Kartanegara sebagai sumber primer yang didukung oleh literatur sekunder berupa buku dan artikel ilmiah relevan. Analisis data dilakukan secara deskriptif, interpretatif, dan komparatif. Hasil penelitian menunjukkan bahwa Seyyed Hossein Nasr menekankan pentingnya scientia sacra, yaitu pengembalian dimensi kesakralan ilmu dan integrasi nilai spiritual dalam sains modern. Sementara itu, Mulyadhi Kartanegara menekankan rekonstruksi epistemologi Islam melalui integrasi indra, akal, dan intuisi (qalb) dalam kerangka tauhid. Penelitian ini menyimpulkan bahwa sintesis pemikiran kedua tokoh tersebut memberikan landasan konseptual yang kuat bagi pembaharuan pendidikan Islam yang holistik, integratif, dan berkeadaban.